Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai di Dinas Koperasi dan Usaha Mikro Kota Depok - Natasya Nada Afrinda (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
Work motivation that is not optimal and a work environment that needs to be improved are factors that need to be considered in efforts to improve employee performance. This study aims to determine the influence of work motivation and work environment on employee performance at the Depok City Cooperative and Micro Business Agency. The study employed a quantitative approach using a saturated sampling involving 53 employees as respondents. Data were collected through interviews, observations, and questionnaires using a Likert scale. Data analysis was conducted using SPSS through validity, reliability, classical assumption test, multiple linear regression, t-tests, F-tests, and coefficient of determination. The results indicate that work motivation does not have a significant effect on employee performance, with a significance value of 0.146 > 0.05. In contrast, the work environment has a positive and significant effect on employee performance, with a significance value of 0.000 < 0.05. Simultaneously, work motivation and work environment significantly affect employee performance. The Adjusted R Square value of 0.351 indicates that both variables explain 35.1% of employee performance, while the remainder is explained by other factors